Viral dialectics - João Pedro Cachopo (O Que Nos Faz Pensar, 2020)
I start with two questions about the Covid-19 pandemic. What does it reveal about us and the reality that surrounds us? How does it transform our forms of life and the world we live in? The multiple interpretations of this crisis, oscillating between optimism and pessimism, emerge from how one intersects the answers to these two questions. In this article, my goal is to map these responses (in dialogue with authors such as Žižek, Butler, Latour, Klein, Badiou, Nancy, among others) while also searching for an untimely way of articulating the two questions. My hypothesis, drastically put, is that the pandemic is not the event. The event is the transformation of the forms of life (or the “twist of the senses”, as I call it elsewhere) that the pandemic already precipitates before one has the opportunity to draw any conclusions, practically or theoretically, about what the pandemic reveals about the world.